2021
DOI: 10.1186/s12891-021-04412-4
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results in anterior cervical discectomy and fusion with the uncovertebral joint fusion cage in a goat model

Abstract: Objective To preliminarily evaluate the safety and efficacy of the uncovertebral joint fusion cage in a goat model of cervical spine interbody fusion. Methods Twenty-four healthy adult goats were randomly assigned to one of the two following groups: Group A, goats were implanted with an uncovertebral joint fusion cage combined with a local autograft and Group B, goats were implanted with a non-profile cage filled with a local autograft. The goats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…As the target fusion area was different between the 2 groups in this trial, we adopted the definition of fusion as "interspinous mobility of £1 mm and formation of a bone bridge in the target area," which evaluated both the local fusion and stability of the operatively treated segment. In a previous goat study 21 , the UJF fusion rate was much higher than the ESF fusion rate at 12 and 24 weeks postoperatively. Micro-CT and bone tissue analysis revealed that osteogenesis in the uncovertebral joint was greater than that in the end-plate space 21 .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…As the target fusion area was different between the 2 groups in this trial, we adopted the definition of fusion as "interspinous mobility of £1 mm and formation of a bone bridge in the target area," which evaluated both the local fusion and stability of the operatively treated segment. In a previous goat study 21 , the UJF fusion rate was much higher than the ESF fusion rate at 12 and 24 weeks postoperatively. Micro-CT and bone tissue analysis revealed that osteogenesis in the uncovertebral joint was greater than that in the end-plate space 21 .…”
Section: Discussionmentioning
confidence: 64%
“…In a previous goat study 21 , the UJF fusion rate was much higher than the ESF fusion rate at 12 and 24 weeks postoperatively. Micro-CT and bone tissue analysis revealed that osteogenesis in the uncovertebral joint was greater than that in the end-plate space 21 . The goat cervical spine resembles the human cervical spine anatomically, making it suitable for spine-related research [29][30][31] .…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, it is necessary to adopt a more rational and individual approach in estimating the maximum stress to failure loads, and we aim to perform relevant targeted optimizations in future studies. In our previous goat model research (Shen et al, 2021), no screw loosening, screw breakage, cage displacement, or subsidence was observed for the uncovertebral joint fusion cage during the 6 months of follow-up. In our prospective, randomized, controlled trial study, there were no cage subsidence and displacement, screw loosening, and fracture in the uncovertebral joint fusion cage group during the 6-month follow-up.…”
Section: Cage Subsidencementioning
confidence: 72%
“…Therefore, we postulated that uncovertebral joint fusion might have potential advantages in cervical spine interbody fusion and designed a novel uncovertebral joint fusion cage. In our previous goat model research ( Shen et al, 2021 ), 75.0% (9/12) of the goats in the uncovertebral joint fusion cage group were evaluated as achieving fusion at 12 weeks when compared to 41.7% (5/12) in the non-profile cage group. Additionally, the fusion grading scores of the uncovertebral joint fusion cage group were significantly higher than those of the non-profile cage group, both at 12 and 24 weeks ( p < 0.05), without increasing serious complications during the 6 months of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Although no significant difference was observed in the fusion rate at 12 months, their results showed that fusion rates at 3 and 6 months after ACDF were much higher in the UJF group than in the ESF group (UJF versus ESF: 66.7% versus 13.2% at 3 months, 94.1% versus 66.7% at 6 months). Based on a previously published goat study 3 , the authors speculated that the reasons for these results were due to several factors. The uncovertebral joint had several anatomical advantages over ESF: a narrower gap, higher mechanical load, better osteogenic potential, and better blood supply, which could be advantageous for earlier cervical fusion.…”
Section: Commentarymentioning
confidence: 99%